KAYU KELAPA SEBAGAI BAHAN INTI PAPAN BLOK - Suwandi Kliwon; Paribotro Sutigno; M I lskandar (Jurnal Penelitian Hasil Hutan, 1986)
This report  deals  with  the  making  of  blackboard   with  coconut   wood  core and  testing  the physical  and  mechanical  properties   of  the blackboard.   The coconut  wood (Cocos nucifera)  was collected from   Banten,  (West  Java).The results, indicate that the physical properties  of blockboard  with coconut  wood core are worse than that with a mixture  of red meranti and coconut  wood core. The bending strength  paralel  to the grain of blockboard  with coconut  wood core is better  than that   with a mixture  of coconut  wood and meranti  wood,  while the properties  perpendicular  to the grain do not show  significant  difference.Only  the glue shear strength  of  blockboard   type  II  with a mixture  of  coconut  wood  and  red meranti  wood  core is in compliance  with Indonesian  and Japanesse  (JAS)  standars.